2023
DOI: 10.15252/embr.202255235
|View full text |Cite
|
Sign up to set email alerts
|

Chemical conversion of human conventional PSCs to TSCs following transient naive gene activation

Abstract: In human embryos, naive pluripotent cells of the inner cell mass (ICM) generate epiblast, primitive endoderm and trophectoderm (TE) lineages, whence trophoblast cells derive. In vitro, naive pluripotent stem cells (PSCs) retain this potential and efficiently generate trophoblast stem cells (TSCs), while conventional PSCs form TSCs at low efficiency. Transient histone deacetylase and MEK inhibition combined with LIF stimulation is used to chemically reset conventional to naive PSCs. Here, we report that chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
2
6
0
Order By: Relevance
“…After 7 days naive compact colonies emerged and were expanded. In EMPTY-iPSCs, resetting gave rise to a mixed population, as previously reported 17,33 , while overexpression of KLF7 resulted in a morphologically homogeneous population of naive colonies (Fig. 5b, left).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…After 7 days naive compact colonies emerged and were expanded. In EMPTY-iPSCs, resetting gave rise to a mixed population, as previously reported 17,33 , while overexpression of KLF7 resulted in a morphologically homogeneous population of naive colonies (Fig. 5b, left).…”
Section: Resultssupporting
confidence: 80%
“…Induction of pluripotency in human somatic cells can be achieved via the expression of different combinations of the factors OCT4, SOX2, KLF4, MYC, NANOG, LIN28A (OSKM and OSNL), which leads to the generation of induced Pluripotent Stem Cells (iPSCs) 4,6 . We verified the absolute expression of such reprogramming factors in several human PSC and iPSC lines by interrogating previously published data 10,12,2733 and observed that expression of the pluripotency factor KLF4 was barely detectable (Fig. 1a).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations